Pricing and coordination of vaccine supply chain based on blockchain technology. Issue 6 (26th July 2021) - Liu, Ruihuan; Tan, Chunqiao; Zhao, Chengwei
Abstract : Purpose: Vaccine safety is a major issue in the world. Blockchain technology is the right solution to this worldwide problem. The impact of introducing blockchain technology on the operational efficiency of the vaccine supply chain is unclear. Therefore, from the perspective of game theory, this paper aims to construct a vaccine supply chain model consisting of a vaccine manufacturer, a vaccine traceability service platform based on blockchain technology and a vaccination unit to discuss its pricing and coordination. Design/methodology/approach: This study analyzes the pricing and coordination of the vaccine supply chain based on blockchain technology, compares the decision-making of fixed charge scenario and proportional charge scenario and reveals the impact of blockchain on the vaccine supply chain. Findings: Results demonstrate that the revenue-sharing contract can coordinate the vaccine supply chain when the proportion of revenue sharing meets certain conditions. The fixed charge scenario is more beneficial to the vaccine supply chain than the proportional charge scenario. The introduction of blockchain technology increases the total profit, consumer surplus and social welfare of the vaccine supply chain. Therefore, the operational efficiency of the vaccine supply chain is improved. Originality/value: This study not only provides important support for enterprises to adopt blockchain technology but also provides some guidance for decision-makers to implement scientific and feasible vaccine supply chain management schemes.